A Method for the Simultaneous Determination of Chlorogenic Acid and Sesquiterpene Lactone Content in Industrial Chicory Root Foodstuffs - Honorine Willeman; Philippe Hance; Anne Fertin; Najia Voedts; Nathalie Duhal; Jean-François Goossens; Jean-Louis Hilbert (The Scientific World Journal)
A method for the simultaneous determination of free chlorogenic acids (CGA) and sesquiterpene lactones (STL) in chicory root and its dried (flour) and roasted (grain) forms is described. The method uses one extraction and one analysis for all chicory root products. Various solvents with low to high polarity, such as methanol, chloroform, or n-hexane, were tested alone, in combination in different proportions or with acidified or neutral aqueous solvent. The water/chloroform/methanol (30/30/40, v/v/v) mixture generated the best extraction yield, 21% higher than alcohol mixtures. The profiling of CGA and STL content was performed through a conventional HPLC-DAD method using a PFP core shell column in a fast single run. Good retention time and area repeatability (RDD mean % 0.46 and 5.6, resp.) and linearity (R2≥0.96) were obtained. The STL and chlorogenic acids levels determined were 254.7 and 100.2 μg/g of dry matter in the root, 792.5 and 1,547 μg/g in flour, and 160.4 and 822.5 μg/g in the roasted grains, respectively. With an average recovery of 106% and precision of 90%, this method is rapid, reproducible, and straightforward way to quantify the chlorogenic acids and STL in chicory raw material and end products.